(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article discusses the main aspects of the prevention of non-communicable diseases (NCDs), including risk factors, modern methods of prevention and the importance of hygiene measures. Particular attention is paid to the primary and secondary prevention of cardiovascular diseases, oncology, diabetes mellitus and chronic respiratory diseases. Data on the impact of lifestyle on the reduction of non-communicable diseases are provided.